Usability Testing Analysis on Digital Wallet Applications to Measure User Satisfaction - Nur Mutia Eka Pusparani; Tyas Setiyorini; Frieyadie Frieyadie (Kresnamedia Publisher, 2023)
One of the issues that users of digital wallet apps often face is slow loading, which can cause frustration and disrupt the user experience. In addition, lack of app responsiveness due to server errors is also a complaint of users, which can lower their trust in the app. Another problem is the difficulty in the login process, which can make it difficult for users to access the application. From these problems, it is necessary to conduct a